Liquid-Liquid Extraction by the Slug Technique - Krovvidi, Rao Kameswara (My University, 1980)
The slug technique proposed by Baird and Ho¹⁶ is a simple and easy way of obtaining the fundamental data on mass transfer coefficients in ternary liquid-liquid extraction. The technique yields a constant measurable interfacial area and the coefficients thus obtained from the experiments could be compared with those obtained by the penetration theory.
The technique, as proposed, operates on a cylindrical slug of the organic phase suspended freely by downflow of water. This is modified in this work, by means of a disc arrangement to accommodate changes in aqueous phase flow rate. It was observed that the disc, which holds the slug at the center of the tube, has also enhanced the mass transfer rates by improving the mixing inside the slug, the improvement being higher for smaller slug lengths.
The mass transfer coefficients in general were found to be lower than the penetration theory values. This could be due to any of the effects of dissolution of the solvent in the aqueous phase, hydrodynamic and surface conditions, variation of phase resistance with time, contaminants, and uncertainity about the distribution coefficient of the system: n-Heptane-Iodine-Water. Mass transfer rates in extraction with reactions were also found to be low and was thought to be due to violation of the assumption that the reaction between iodine and sodium thiosulphate is instantaneous. In the experiments with acetic acid as the solute, transfer rates were found to be higher than the expected because of Marangoni effects induced by the solute. It was concluded, however, that the technique will still be useful in obtaining the fundamental data with the use of a system with well-defined distribution data and redistilled solvents.
Keywords: Chemical Engineering; Chemical Engineering